- 1-800-665-6601
- [email protected]

In Substitution method, either ‘x’ or ‘y’ can be chosen to be written in terms of the other.

Given x+ y = 6=>y= 6- x

Now substitute this value of ‘y’ in the second equation, x– y = 2.

This gives: x- (6- x) = 2=> x- 6 + x = 2=> 2x = 6+ 2

This gives: x= 8/2=>x = 4.

Now y = 6- x ==> y= 6– 4=> y = 2.

In Substitution method, either ‘x’ or ‘y’ can be chosen to be written in terms of the other.

Given x+ y = 11=> x= 11- y

Now substitute this value of ‘x’ in the second equation, x– y = 7.

This gives: (11 – y) – y = 7=> 11- y- y = 7=> 11- 2y= 7=>2y= 11- 7

This gives: y= 4/2=> y= 2.

Now x= 11 - y==> x= 11– 2=> x= 9.